2020
DOI: 10.1186/s42238-019-0014-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabis oil extract on immune response gene expression in human small airway epithelial cells (HSAEpC): implications for chronic obstructive pulmonary disease (COPD)

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is commonly associated with both a pro-inflammatory and a T-helper 1 (Th1) immune response. It was hypothesized that cannabis oil extract can alleviate COPD symptoms by eliciting an anti-inflammatory Th2 immune response. Accordingly, the effects of cannabis oil extract on the expression of 84 Th2 and related immune response genes in human small airways epithelial cells (HSAEpC) were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…This gene has also been reported to be differentially expressed in airway tissues and participates in the inflammatory response in lung and airway tissues during the pathogenesis of asthma ( Sangaphunchai et al, 2020 ). It has been directly reported to be functionally correlated with IL-13 ( Higham et al, 2020 ; Min et al, 2020 ) and IL-17 ( Kamijo et al, 2020 ; Mamber et al, 2020 ) in focal regions surrounding airway smooth muscles at the transcriptomics level and is further pathologically correlated with several chronic lung diseases, including chronic obstructive pulmonary diseases ( Min et al, 2020 ). Therefore, given its functional correlation with the potential regulatory effects of IL-13 and IL-17 on airway smooth muscle inflammation, the predicted gene CCL26 is definitely an effective signature for cell classification on the transcriptomics level.…”
Section: Discussionmentioning
confidence: 99%
“…This gene has also been reported to be differentially expressed in airway tissues and participates in the inflammatory response in lung and airway tissues during the pathogenesis of asthma ( Sangaphunchai et al, 2020 ). It has been directly reported to be functionally correlated with IL-13 ( Higham et al, 2020 ; Min et al, 2020 ) and IL-17 ( Kamijo et al, 2020 ; Mamber et al, 2020 ) in focal regions surrounding airway smooth muscles at the transcriptomics level and is further pathologically correlated with several chronic lung diseases, including chronic obstructive pulmonary diseases ( Min et al, 2020 ). Therefore, given its functional correlation with the potential regulatory effects of IL-13 and IL-17 on airway smooth muscle inflammation, the predicted gene CCL26 is definitely an effective signature for cell classification on the transcriptomics level.…”
Section: Discussionmentioning
confidence: 99%
“…Phytocannabinoids. Phytocannabinoids derived from Cannabis sativa, such as cannabidiol (CBD) and 9-tetrahydrocannabinol (THC), have been shown to inhibit inflammatory and Th1 cytokines and/or promote anti-inflammatory and Th2 immune responses both in vitro and in vivo (27)(28)(29). As COVID-19 represents a respiratory disease with a dominant Th1 and inflammatory immune response profile, it has been postulated that cannabinoids represent a class of compounds with the potential to alleviate COVID-19 symptoms and severity by helping to decrease inflammation and restore a Th1/Th2 balance in the immune system.…”
mentioning
confidence: 99%
“…There were also certain genes involved in mucus overproduction or hypersecretion that were downregulated. These included the CLCA1 gene (encoding chloride channel accessory 1) and the CMA1 gene (encoding mast cell chymase 1) (29). Preliminary in vivo testing in Caribbean vervet monkeys (Chlorocebus aethiops sabaeus) indicated that the oil extract improved inspiratory lung functions (J. Osborn, University of Kentucky, unpublished data).…”
mentioning
confidence: 99%
“…Phytocannabinoids derived from Cannabis sativa, such as cannabidiol (CBD) and 9tetrahydrocannabinol (THC) have been shown to inhibit inflammatory and Th1 cytokines and/or promote an anti-inflammatory and Th2 immune response both in vitro and in vivo(23)(24)(25). As COVID-19 represents a respiratory disease with a dominant Th1 and inflammatory immune response profile, it has been postulated that cannabinoids represent a class of compounds with the potential to alleviate COVID-19 symptoms and severity by helping to decrease inflammation and restore a Th1/Th2 balance in the immune system.…”
mentioning
confidence: 99%
“…There were also certain genes involved in mucus overproduction or hypersecretion that were downregulated. These included CLCA1 (encoding chloride channel accessory 1) and CMA1(encoding mast cell chymase 1)(25). Preliminary in vivo testing in Caribbean Vervets (Chlorocebus aethiops sabaeus) indicated that the oil extract improved inspiratory lung functions (J. Osborn, University of Kentucky, manuscript in preparation).…”
mentioning
confidence: 99%